Patentability of computer-implemented simulation methods − Connor as an example of the European patent law creation process - Kujansuu, Isa (My University, 2020)
At the European Patent Office (EPO), the Boards of Appeal have been tasked with interpreting the European Patent Convention (EPC) in accordance with technological developments. This work sets out to assess whether or not computer-implemented simulation methods are patentable under the EPC. To answer this question, delineation of relevant EPO Boards of Appeal case law pertaining to computer-implemented inventions (CII) leading up to decision T 0489/14 (CONNOR) and the following referral to the Enlarged Board of Appeal, pending at the time of writing, shall be analysed. The Boards of Appeal have through a case-by-case approach established that the technical character of a CII is an essential requirement of its patentability. However, case law reveals that the Boards of Appeal have adopted multiple contradictory interpretations what constitutes it and also demonstrated willingness to expand the scope of patentability for certain types of inventions. Considering the increasing importance of simulation methods to various industries and technologies, the Board of Appeal in Connor positing a requirement for technical effect in the form of “direct link with physical reality” for simulation methods appears significant. Hence, this thesis also sets out to inquire whether the referral is a genuine inquiry as to the technicality of computer-implemented simulation methods, or whether it is a patent policy question in the sense that the Board of Appeal is deliberately looking into ways to narrow the scope of patentability of simulation-based inventions. In order to answer the question, the EPO’s role in shaping European patent policies shall also be examined. Ultimately, this thesis concludes that the notion of technology in the EPC should not be a static one but one that evolves alongside actual technological developments − necessitating a level of flexibility for the Boards of Appeal in interpreting the EPC. However, due to the institutional design and opacity of the decision-making processes, there is considerable uncertainty with regard to patentability of computer-implemented simulation methods. Some remedies suggested in legal literature, such as increasing participatory opportunities outside appeal proceedings, will be discussed.
Keywords: European Patent Office, computer-implemented invention, computer-implemented simulation method, intellectual property law, inventive step, patent law